The analysis of the patients taken to emergency service by 112 Emergency Healthcare Services: a prospective clinic study - Kaynak, Mahmut Firat; Gafurogullari, Sibel; Deniz, Zulfi Engin; Ozkan, Havva Ozge; Askin Bas, Esra (The European Research Journal, 2017)
Objectives. The aim of this study was to analyze the cases transferred by 112 emergency healthcare services (EHS) according to the triage criteria of Turkish Ministry of Health.Methods. All of the patients brought to adult emergency service unit of our hospital between April 01, 2015 and May 01, 2015 by 112 EHS have been involved in this study. The triage tags of the patients have been determined according to the criteria specified in T.R. Ministry of Health’s “Procedures and principles of emergency health services in inpatient healthcare facilities” dated October 16, 2009. The end of emergency service process has been classified as discharge, hospitalization in service, transfer to another healthcare center, and excitus.Results. A total of 1,101 patients have been involved in this study. The mean age was 45.6 years. The age range was 1-94 years. While 545 (49.50%) patients were female, 556 (50.49%) were male. The portion of Red area was 15.16% (n=167), that of Yellow 1 area 34.60% (n=381), that of Yellow 2 area 23.34% (n=279), and that of Green area 24.80% (n=274). The distribution of the patients by treatment results was as follows; discharge 86.46% (n=952), hospitalization in service 10.08% (n=111), hospitalization in intensive care 2.27% (n=25), transfer to another healthcare center 0.63% (n=7), excitus 0.5% (n=6). The total share of the 65 year-old or older cases was 23.88% (n=263). The distribution of the red area patients by triage was as the following; 47.30% (n=79) hospitalization in service, 10.7% (n=18) hospitalization in intensive care unit, 33.53% (n=56) discharge, 3.59% (n=6) exitus and 4.19% (n=7) transfer to another healthcare service. Conclusions. The inappropriate use of 112 EHS is very common. Majority of the patients taken into emergency service by 112 EHS does not require urgency. After the triage in the ambulance, the patients can be directly transferred to an appropriate field without creating a time and work load on emergency service. Moreover, after the triage in ambulance, the patients requiring the hospitalization may be transferred to the appropriate facility according to the available bed capacity.